2017
DOI: 10.3747/co.24.3420
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Survival in Patients with Brain Metastases from Non-small-Cell Lung Cancer Treated before and after Implementation of Radiosurgery

Abstract: Introduction Survival after a diagnosis of brain metastasis in non-small-cell lung cancer (nsclc) is generally poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(67 reference statements)
2
11
0
1
Order By: Relevance
“…Harris et al reported that the general survival of GK radiosurgery did not differ with respect to sex and previous WBRT applications (15). Similar to our study, many studies have shown better survival among women than men (2,13,26). Although the survival of disease (35,42).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Harris et al reported that the general survival of GK radiosurgery did not differ with respect to sex and previous WBRT applications (15). Similar to our study, many studies have shown better survival among women than men (2,13,26). Although the survival of disease (35,42).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, the median OS was the highest among patients with breast cancer compared with that of patients with lung cancer and other cancer types (13,15,26). In another study, no difference was reported between the OSs of patients KPS scores was not statistically significant according to the different treatments (p>0.05).…”
Section: Survival Analysissupporting
confidence: 87%
“…While Dr. Souza and Sofia were willing to navigate the side effects when Sofia first enrolls, the risks increase once Sofia's cancer metastasises to her brain, which is a relatively common development for lung cancers (see Ali et al 2013, Greenspoon et al 2017. This case highlights how difficult it is to communicate the uncertainty and risk of clinical trials when also trying to account for cancer progression.…”
Section: The Uncertain Consequences Of Trial Drugsmentioning
confidence: 99%
“…Mozgové metastázy (MTS) sú hlavnou príčinou morbidity a mortality pa cientov s onkologickým ochorením [3]. Medián celkového prežívania (over all survival -OS) s mozgovými MTS je od 3,4-12,1 mesiaca [3,[5][6][7]. Vo všeobecnosti sa udáva, že postihnutie centrálnej nervovej sústavy (CNS) má už iniciálne 7,4 % chorých, počas ochorenia počet vzrastie na 23-30 % [6].…”
Section: úVodunclassified